Nutrient and bioactive compounds from Neltuma spp. seeds - Cittadini, M. Cecilia (2024)
Fil: Cittadini, M. Cecilia. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.